2017
DOI: 10.1007/s12253-017-0262-y
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Vascular Patterns in Different Subtypes of Renal Cell Carcinoma. A Morphometric Study in Two Distinct Types of Blood Vessels

Abstract: To analyze the presence of mature and immature vessels as a prognostic factor in patients with renal cell carcinoma and propose a classification of renal cancer tumor blood vessels according to morphometric parameters. Tissue samples were obtained from 121 renal cell carcinoma patients who underwent radical nephrectomy. Staining with CD31 and CD34 was used to differentiate between immature (CD31+) and mature (CD34+) blood vessels. We quantified the microvascular density, microvascular area and different morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…In contrast to the metastatic potential of CCRCC, ccpRCC shows an indolent behavior; therefore, accurate tumor classification is very important for patients' management and prognosis. Different studies have evaluated the prognostic significance of tumor vascularity in renal cell tumors with two different approaches, either quantification of microvessels by histomorphometry (MVD) [20][21][22][31][32][33][34], or vascular architectural patterns [33,35]. Although Weidner et al [24] have reported that von Willebrand and factor VIII are the most specific vascular markers for measuring intratumoral MVD in solid tumors, they acknowledged that CD31 and CD34 are more sensitive.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast to the metastatic potential of CCRCC, ccpRCC shows an indolent behavior; therefore, accurate tumor classification is very important for patients' management and prognosis. Different studies have evaluated the prognostic significance of tumor vascularity in renal cell tumors with two different approaches, either quantification of microvessels by histomorphometry (MVD) [20][21][22][31][32][33][34], or vascular architectural patterns [33,35]. Although Weidner et al [24] have reported that von Willebrand and factor VIII are the most specific vascular markers for measuring intratumoral MVD in solid tumors, they acknowledged that CD31 and CD34 are more sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…The microscopic assessment of vascular architectural patterns was based on four patterns, highlighted by CD34, derived from Ruiz-Saurí et al [33] model, based on the shape of vessels, presence of lumen, and interconnection, and modified as follows:…”
Section: Vascular Architectural Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…The microvascular density, i.e., the surface density of capillaries on the two-dimensional histological section, is commonly used to description of the microvascular network. Changes of the microvascular network are associated with several pathologies including cardiovascular diseases [3], metabolic syndrome [4], and tumors [5].…”
Section: Introductionmentioning
confidence: 99%